Beyond words movement observation and analysis - Moore, Carol-Lynne; Yamamoto, Kaoru (Routledge, 2012)
"Beyond Words presents movement observation and analysis techniques to examine every day human interactions, allowing performers to understand them in a new light.Carol-Lynne Moore and Kaoru Yamamoto build on the techniques they expertly displayed in the first edition of the book, maintaining a focus on the process of movement as opposed to discussions of static body language. The authors combine textual discussion with a new set of website-hosted video instructions to help readers develop an in-depth understanding of nonverbal communication.This new second edition is fully revised with a new introduction, and is illustrated throughout. It presents a fascinating insight into this vital field of study and will be an invaluable resource for scholars and practitioners in many areas of performance analysis, choreography and actor training"--Provided by publisher.